THE INFLUENCE OF PRODUCT QUALITY, PRICE, AND SERVICE QUALITY ON PURCHASING DECISIONS FOR SALAD WRAP AT CRUNCHÄUS SURABAYA - J.E Sutanto; Olivia Surya Hartono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Crunchaus is a business engaged in food and beverages with healthy food products cooked without oil with the flagship product of salad wrap which was established in 2017. Crunchaus has a total of ten outlets in Surabaya and three outlets in Jakarta. Based on the testimonials of consumers who visited Crunchaus Surabaya on Google Reviews, there are various problems related to the lack of quality of the products provided, the price of products that are called expensive, and the lack of service quality. The purpose of this study was to determine the effect of product quality, price, and service quality on purchasing decisions for salad wraps at Crunchaus Surabaya. The method in this research is descriptive quantitative, with multiple linear regression analysis using the Stastical Program for Social Science (SPSS). Data collection in this study used a research instrument in the form of a Google Form with a sample size of 210 respondents who are Crunchaus Surabaya consumers with the criteria of having purchased salad wrap at Crunchaus Surabaya at least once in the period 2023-2024 and domiciled in Surabaya. The independent variables in this study are product quality (X1), price (X2), and service quality (X3). The dependent variable in this study is the purchase decision (Y) This study shows that product quality, price, and service quality have a significant and positive influence on purchasing decisions of Crunchaus Surabaya consumers.